Polymers and Composites for Energy Storage Applications - Chen Mei; Wang Jing; Sun Wei (Research of Scientia Naturalis, 2024)
The increasing demand for efficient energy storage solutions has driven research into polymers and composites. These materials offer unique advantages, such as lightweight properties, flexibility, and tunable conductivity, making them ideal candidates for energy storage applications. The exploration of innovative polymers and composites is essential for improving energy density and cycle life in storage devices. This research aims to evaluate the performance of various polymers and composites in energy storage applications. The focus is on understanding their electrochemical properties and how modifications can enhance their performance in batteries and supercapacitors. A systematic review of recent advancements in polymer and composite materials was conducted, alongside experimental assessments of selected materials. Performance metrics such as conductivity, energy density, and stability were evaluated using electrochemical testing methods, including cyclic voltammetry and galvanostatic charge-discharge tests. The findings indicate that specific polymers and composites exhibit enhanced performance in energy storage applications. Notable improvements in conductivity and energy density were observed, particularly with the incorporation of conductive fillers. Additionally, the stability of the materials under cycling conditions showed promising results, suggesting their potential for practical applications.The research highlights the significant potential of polymers and composites in advancing energy storage technologies. Continued exploration and optimization of these materials can lead to the development of more efficient and durable energy storage solutions, addressing the growing demands for sustainable energy systems.